Widespread support for a global species list with a formal governance system - Lien, Aaron M. (2023)
Taxonomic data are a scientific common. Unlike nomenclature,which has strong governance institutions, there are currentlyno generally accepted governance institutions for thecompilation of taxonomic data into an accepted global list.This gap results in challenges for conservation, ecologicalresearch, policymaking, international trade, and other areasof scientific and societal importance. Consensus on a globallist and its management requires effective governance andstandards, including agreed mechanisms for choosingamong competing taxonomies and partial lists. However,governance frameworks are currently lacking, and a callfor governance in 2017 generated critical responses. Anygovernance system to which compliance is voluntary requiresa high level of legitimacy and credibility among those by andfor whom it is created. Legitimacy and credibility, in turn,require adequate and credible consultation. Here, we reporton the results of a global survey of taxonomists, scientistsfrom other disciplines, and users of taxonomy designed toassess views and test ideas for a new system of taxonomiclist governance. We found a surprisingly high degree ofagreement on the need for a global list of accepted speciesand their names, and consistent views on what such a listshould provide to users and how it should be governed. Thesurvey suggests that consensus on a mechanism to create,manage, and govern a single widely accepted list of all theworld’s species is achievable. This finding was unexpectedgiven past controversies about the merits of list governance.